To perform the operation and simplify the expression \((4 - 2x) \frac{-6x^2 + 10x + 21}{4 - 2x}\), notice that the \( (4 - 2x) \) in the numerator and denominator will cancel out, as long as \( 4 - 2x \neq 0 \) (which occurs at \( x = 2 \)).
The operation simplifies as follows:
\[ (4 - 2x) \frac{-6x^2 + 10x + 21}{4 - 2x} = -6x^2 + 10x + 21 \]
Now we will check if \(-6x^2 + 10x + 21\) can be further simplified or factored.
To do that, let's look for roots or factors. We can use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = -6, b = 10, c = 21 \):
\[ b^2 - 4ac = 10^2 - 4(-6)(21) = 100 + 504 = 604 \]
Since \( 604 \) is not a perfect square, the quadratic does not factor nicely into integers.
Thus, the expression \(-6x^2 + 10x + 21\) does not simplify further, and we are left with:
\[ -6x^2 + 10x + 21 \]
The final answer is:
\(-6x^2 + 10x + 21\)